Listeria monocytogenes Methods and Protocols - Jordan, Kieran; Fox, Edward M.; Wagner, Martin; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Humana, 2014)
Listeria monocytogenes is still a major threat to public health. A new book in the Methods in Molecular Biology series, Listeria monocytogenes: Methods and Protocols addresses its titular pathogen with protocols and methodologies used in research to gain a better understanding of Listeria at a molecular level. The topics covered include sampling in order to isolate Listeria, methods for their identification and characterization, methods for gene manipulation, and, finally, methods for control of the organism. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective subjects, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls.   Vital and authoritative, Listeria monocytogenes: Methods and Protocols aims to contribute to the harmonization of the methods used in the field and will therefore benefit all those interested in Listeria research.
Sampling the Production/Processing Environment for Listeria -- Traditional Methods for Isolation of Listeria monocytogenes -- Confirmation of Isolates of Listeria by Conventional and Real-Time PCR -- Serotype Assignment by Sero-Agglutination, ELISA and PCR -- Pulsed-Field Gel Electrophoresis (PFGE) Analysis of Listeria monocytogenes -- Multi-Locus Sequence Typing (MLST) of Listeria monocytogenes -- Ribotyping and Automated Ribotyping of Listeria monocytogenes -- Fluorescent Amplified Fragment Length Polymorphism (fAFLP) Analysis of Listeria monocytogenes -- High-Throughput Characterization of Listeria monocytogenes Using the OmniLog Phenotypic Microarray -- Analysis of Listeria monocytogenes Subproteomes -- The Listeria Cell Wall and Associated Carbohydrate Polymers -- Use of Bacteriophage Cell Wall Binding Proteins for Rapid Diagnostics of Listeria -- Virulence Characterization of Listeria monocytogenes -- Internalization Assays for Listeria monocytogenes -- Extraction and Analysis of Plasmid DNA from Listeria monocytogenes -- Generation of Non-Polar Deletion Mutants in Listeria monocytogenes Using the “SOEing” Method -- Mutant Construction and Integration Vector-Mediated Gene Complementation in Listeria monocytogenes -- Absolute and Relative Gene Expression in Listeria monocytogenes Using Real Time PCR -- Genome Sequencing of Listeria monocytogenes -- Using Enhanced Green Fluorescent Protein (EGFP) Promoter Fusions to Study Gene Regulation at Single Cell and Population Levels -- Control of Listeria monocytogenes in the Processing Environment by Understanding Biofilm Formation and Resistance to Sanitizers -- Vaccination Studies: Detection of a Listeria monocytogenes Specific T Cell Immune Response Using the ELISPOT Technique -- Sampling the Food Processing Environment: Taking up the Cudgel for Preventive Quality Management in Food Processing Environments.
Keywords: Microbiology; Food—Biotechnology.; Microbiology; Food Science